Determinants of Auditor Performance - Hernando, Riski; Prasetyo, Eko; Yuli Sari, Rizki (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
Purpose – This research was conducted using a quantitative approach to test the direct influence relationships on factors affecting auditor performance. Methodology/approach – The sample used in this study consisted of 124 government auditors as respondents from various Districts/Cities in the Province of Jambi. Data were analyzed using the Structural Equation Modeling (SEM) PLS approach with Warp-PLS software, both in the measurement model and structural model. Findings – The research findings indicate that out of the six direct hypotheses proposed, two hypotheses significantly influence auditor performance, namely, information technology and role clarity. Meanwhile, competence, independence, organizational commitment, and role ambiguity do not have a significant impact on auditor performance. Novelty/value – This research involves the role of information technology in the inspectorate auditor's process and also includes psychological factors affecting the performance of inspectorate auditors.